Optimization of parameters in the fermentation of soapnuts using Saccharomyces cerevisiae via response surface methodology - Truong, Thi Chien; Ngo, Thi Thanh Huyen; Dao, Ngoc Anh; Nguyen, Thi Thanh Mai; Tran, Bao Tram; Vu, Xuan Tao (Vietnam Journal of Biotechnology, 2026)
Soapnuts represent a promising natural source of surface-active compounds for the development of eco-friendly bio-detergents as alternatives to conventional chemical-based cleaning products. Currently, soapnuts are recognized as a major saponin-rich raw material for producing various bio-based cleansing products such as shampoos, soaps, body washes, and dishwashing liquids. Soapnut extracts, which are rich in saponins, have been demonstrated to exhibit multiple biological activities, including anticancer, antifungal, antibacterial, and anti-inflammatory effects. Moreover, saponins from soapnuts also show strong cleansing properties. These characteristics make soapnuts a promising raw material for the development of green detergent products that are safer for human health. This study aimed to optimize several parameters in the fermentation process of soapnuts using Saccharomyces cerevisiae, employing response surface methodology (RSM) to obtain a fermented extract with the highest possible saponin-to-total soluble solids (TSS) ratio. The multi-factor experimental plan employed the Box-Behnken planning model with three independent variables corresponding to the following variation ranges: inoculum size (1-15%), fermentation temperature (25-35ºC), and fermentation time (2-8 days), with the objective function being the saponin/TSS content (%). Experimental results revealed that the optimal conditions for achieving the highest saponin/TSS content (85.1%) were an inoculum size of 9%, a fermentation temperature of 32°C, and a fermentation duration of 5 days. The fermented extract exhibited strong antibacterial activity against three pathogenic bacterial strains: Escherichia coli VTCC12272, Bacillus cereus SH46, and Staphylococcus aureus VTCC12275, with mean inhibition zone diameters of 20.5, 15.3, and 28.2 mm, respectively. The fermented extract from soapnut exhibited a high saponin/TSS content. It demonstrated significant antimicrobial activity, indicating its strong potential as a valuable raw material for the development of natural bio-detergent products.